A quantitative survey measure of moral evaluations of patient substance misuse among health professionals in California, urban France, and urban China - Anna Yu Lee; Curtis Lehmann; Pengchong Zhou; Bin Xie; Kim D. Reynolds; Alan W. Stacy (Philosophy, Ethics, and Humanities in Medicine, 2023)
Abstract Background The merits and drawbacks of moral relevance models of addiction have predominantly been discussed theoretically, without empirical evidence of these potential effects. This study develops and evaluates a novel survey measure for assessing moral evaluations of patient substance misuse (ME-PSM). Methods This measure was tested on 524 health professionals (i.e., physicians, nurses, and other health professionals) in California (n = 173), urban France (n = 102), and urban China (n = 249). Demographic factors associated with ME-PSM were investigated using analyses of variance (ANOVAs) and t-tests, with results suggesting that ME-PSM is higher among younger health professionals, nurses (when compared with physicians and other health professionals), and Chinese health professionals (when compared with French and American health professionals). Results Results provide preliminary support for the psychometric quality of the survey measure introduced in this study, including the existence of a single latent structure and partial invariance of collected data across countries. Conclusion The survey measure for ME-PSM which was developed and tested in the current study appears to hold potential utility for use as a measure of moral views of patient substance misuse. With development, this measure may be used to examine moral evaluations, both as factors of stigma and of other clinical factors associated with the treatment of patients with substance use disorders.